The effectiveness of non-pharmacological interventions in improvement of sleep quality among non-remissive cancer patients: A systematic review of randomized trials - Fadli, Fatmawati; Budworth, Luke (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2016)
Statistical results estimated that most of non-remissive cancer patients face sleep problem and experience the symptoms of insomnia throughout and after the completion of cancer treatment. The purpose of this review was to compare the effectiveness between several types of non-pharmacological interventions and standard care or treatment to improve the sleep quality among non-remissive cancer patients. All randomized studies focused on non-pharmacological interventions to improve sleep quality among non-remissive cancer patients were included. Thirteen studies were selected with a total of 1,617 participants. The results found that only four interventions were significantly effective to improve sleep quality among non-remissive cancer patients, included cognitive behavioral therapy, relaxation and guided imagery program, self-care behavior education program, and energy and sleep enhancement program.